Kualitas Audit sebagai Pemediasi Ukuran Perusahaan, Ukuran Dewan Komisaris, dan Jenis Kelamin CEO terhadap Fee Audit - Destiur Krisnasari Simatupang; Tubagus Ismail; Muhamad Taqi (AFRE (Accounting and Financial Review), 2021)
This study aims to examine the effect of firm size, board of commissioners size, and CEO gender on external auditor fees with audit quality as a mediating variable in banking companies. This study uses secondary data from the annual reports of all banking companies. The sample of this study consisted of 15 banking companies listed on the Indonesia Stock Exchange in 2014-2019 using the purposive sampling method as the research method and using multiple linear regression analysis models and Sobel tests. The results show that the size of the company and the size of the board of commissioners and audit quality partially have a significant effect on external audit fees, and company size on audit fees with audit quality as a mediating variable. While the gender of the CEO has no effect on external audit fees, company size, the size of the board of commissioners, and the gender of the CEO have no effect on audit quality, as well as the size of the board of commissioners, the gender of the CEO has no effect on audit fees with audit quality. as a mediating variable.DOI: https://doi.org/10.26905/afr.v4i2.6511